On the impact of external debt and aid on public expenditure allocation in sub-Saharan Africa after the launch of the HIPC initiative - Maria Quattri; Kwasi Fosu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
In the wake of the current financial and economic crises, the economies of sub-Saharan Africa find themselves squeezed between likely reductions in official development assistance and the pressing challenge to eradicate poverty. Public expenditure allocation to the social sector and to public investment is constrained by the need to pursue fiscal discipline in order to avert debt distress. Within a framework of public expenditure choice, the paper investigates the impact of the external debt-servicing constraint, as well as external aid, on government expenditure allocation in sub-Saharan Africa countries after the launch of the Heavily Indebted Poor Countries Initiative. Among the findings are: (i) the debt effect, while substantially lower than existing estimates for the pre-HIPC period, remains negative for the social sector, with education expenditure funding gaps, suggesting that appropriate measures must be undertaken in order to prevent the deleterious effects of debt, particularly on the social sector. Meanwhile, the additional finding that government effectiveness favours public investment as well as spending in the social sector suggests that increased attention on governance is called for.
Keywords: F34; F35; H51; H52; H54; O55; 330; SSA; HIPC; public expenditure allocation; external debt and aid; Internationale Staatsschulden; Entwicklungshilfe; Schuldenmanagement; HIPC-Initiative; Afrika südlich der Sahara